MANAJEMEN KONFLIK MAHASISWA SEBAGAI METODE PEMBELAJARAN ALTERNATIF - Miyarso, Estu (MAJALAH ILMIAH PEMBELAJARAN, 2007)
Indonesia is the plural state. Campus life represent the manivestasi from the plural state life. Student as component and subjek study are represent the barometer mount the pluralitas in a certain college community. Pluralitas represent the social potency which not yet many developed in our life activity especially in study activity. This matter pushing the importance conducted by research of method conflict management base on the pluralitas of self potency for the Education of Pancasila lecturing as source of this article. From research result which have been conducted known, that the conflict management can be made alternative method of study in lecturing activity, pluralitas of self potency had by student in a community at the class represent the social potency be able to developed in method of this conflict management study.